X-Ray CT Imaging of Grease Behavior in Ball Bearing and Numerical Validation of Multi-Phase Flows Simulation - Takashi Noda (Japanese Society of Tribologists, 2020)
In an effort to further extend bearing life, the authors have attempted to acquire greater knowledge regarding lubricating grease behavior in a bearing. While conducting experiments, some kinds of difficulties commonly arise when attempting to observe grease behavior directly from the bearing exterior without removing seals and shields. Making a breakthrough such a troubling aspect, X-ray computed tomography (CT), which is one of the non-destructive inspection techniques, was employed and resulted in visualizing remarkable details of grease distribution in a resin ball bearing. Hydrodynamic grease transition from churning to channeling state was well revealed by the mixture distribution of urea and barium-based greases which have different properties of X-ray absorption capability. Furthermore, the three dimensional unsteady liquid-gas multi-phase flows analysis was performed. Hydrodynamic feature of grease was regarded as a non-Newtonian fluid, which shows a highly non-linear flow curve, and the constitutive equation of modified Bingham plastic model proposed by Papanastasiou was applied to rheological property. Through these novel experimental and calculation approaches, several new insights about grease behavior inside a ball bearing were brought out.